Peran Ganda Mahasiswa STDI Imam Syafi’i Jember Berkeluarga Sebagai Kepala Keluarga dan Tholibul Ilmi - Nur Baiti Hidayah (USRAH: Jurnal Hukum Keluarga Islam, 2024)
Education and marriage are noble acts of worship in the sight of Allah. It is common for young people to get married after completing their undergraduate education, but there are those who get married before completing their university studies, one of the aims of which is to avoid the sin of adultery and its intermediaries. Having a dual role as head of the family and tholibul ilmi is a great combination of worship to Allah Ta'ala. This research aims to open people's minds so that they do not feel hesitant to take the level of marriage with their condition as tholibul ilmi, because in fact there is no limit to learning and marriage is not a barrier to continuing education at a higher level. This research is a qualitative study that combines field and library research methods to obtain research data. The results of this study indicate that dual role owners must be able to divide time for each role and obligation, they must also have strategies to deal with challenges and conflicts that occur, they also have an afterlife orientation as a motivation in studying religious knowledge, and the importance of religious knowledge in family life, especially in children's education. Keywords:  Dual Role; Head of the Family; Knowledge Claimant.